Berlin Unter Grund: Vision beyond the surface city. (2nd March 2023) - Olsson Berggren, Mikael
Abstract: This article examines a selection of poetry and short prose depicting U‐Bahn journeys in early 20th‐century Berlin. While the cultural imagination of Berlin's emergence as a modern metropolis in the late 19th and early 20th centuries is closely intertwined with the historical novelty of exterior spaces in the city and the figure of the perambulating flaneur, the cityscape's underground, made up of U‐Bahn tunnels and thousands of passengers have figured much less prominently in scholarship on Berlin's modernity. The close readings focus on the texts' mediation of the sensory experience of underground dwelling and the impact of the sudden shifts between above‐ and belowground environments on the passenger's perception of space. As the article shows, the visual imagination and literary tropes that we encounter in the U‐Bahn signify not only modes of representing modern urban space but also hold significance for understanding the importance of threshold experiences in modernity.